2007
DOI: 10.1080/00365520600881193
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of endoscopy for the diagnosis of giardiasis and other intestinal diseases in patients with persistent diarrhea from tropical or subtropical areas

Abstract: Compared to stool examinations using DFA, upper endoscopy is less sensitive for the diagnosis of giardiasis. In patients with negative stool examinations, lower endoscopy yields relevant diagnoses more often than upper endoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 18 publications
1
17
0
6
Order By: Relevance
“…Colonoscopy has been considered in the evaluation of the patient with persistent diarrhea. In a recent study looking at the diagnostic value of endoscopy for the diagnosis of giardiasis or other intestinal diseases in patients with persistent diarrhea returning from tropical or subtropical areas, lower endoscopy (colonoscopy or sigmoidoscopy) yielded relevant diagnoses more oft en than upper endoscopy ( 163 ). Th is study, however, suff ers from a small sample size insofar as only 31 patients with persistent diarrhea were examined and thus the additional value of such procedures cannot be recommended.…”
Section: Summary Of Evidencementioning
confidence: 82%
“…Colonoscopy has been considered in the evaluation of the patient with persistent diarrhea. In a recent study looking at the diagnostic value of endoscopy for the diagnosis of giardiasis or other intestinal diseases in patients with persistent diarrhea returning from tropical or subtropical areas, lower endoscopy (colonoscopy or sigmoidoscopy) yielded relevant diagnoses more oft en than upper endoscopy ( 163 ). Th is study, however, suff ers from a small sample size insofar as only 31 patients with persistent diarrhea were examined and thus the additional value of such procedures cannot be recommended.…”
Section: Summary Of Evidencementioning
confidence: 82%
“…Some authors have reported that the yields of the microscopic examination of duodenal aspirates vary from 0.7 to 47.6% [32] . However, some diagnostic limitations for the isolation of G. intestinalis trophozoites in duodenal aspirates have been reported by Wahnschaffe et al [33], who detected G. intestinalis in duodenal aspirates examined by direct fluorescent-antibody assays in only 3 patients, whereas 16 patients demonstrated the faecal excretion of Giardia cysts.…”
Section: Discussionmentioning
confidence: 99%
“…122 The sensitivity of duodenal aspirates taken during upper endoscopy is low (20%), and its routine use for diagnosis of infection is of questionable value. 123 In patients with a non-acidic gastric environment secondary to acid suppressive therapy, gastric surgery, duodenogastric reflux, Helicobacter pylori infection, and atrophic gastritis, giardiasis rarely may involve the stomach; in one such case, markedly erythematous antral mucosa with small, patchy, cotton-like lesions was described. 124 Histologic findings Giardiasis typically is diagnosed via stool examination, fecal immunoassays, and/or tissue biopsy.…”
Section: Endoscopic Findingsmentioning
confidence: 98%